ZnT3 mRNA levels are reduced in Alzheimer's disease post-mortem brain - Beyer, Nancy (BioMed Central, 2009)
BACKGROUND: ZnT3 is a membrane Zn(2+ )transporter that is responsible for concentrating Zn(2+ )into neuronal presynaptic vesicles. Zn(2+ )homeostasis in the brain is relevant to Alzheimer's disease (AD) because Zn(2+ )released during neurotransmission may bind to Aβ peptides, accelerating the assembly of Aβ into oligomers which have been shown to impair synaptic function. RESULTS: We quantified ZnT3 mRNA levels in Braak-staged human post mortem (pm) brain tissue from medial temporal gyrus, superior occipital gyrus, superior parietal gyrus, superior frontal gyrus and cerebellum from individuals with AD (n = 28), and matched controls (n = 5) using quantitative real-time PCR. ZnT3 mRNA levels were significantly decreased in all four cortical regions examined in the AD patients, to 45-60% of control levels. This reduction was already apparent at Braak stage 4 in most cortical regions examined. Quantification of neuronal and glial-specific markers in the same samples (neuron-specific enolase, NSE; and glial fibrillary acidic protein, GFAP) indicated that loss of cortical ZnT3 expression was more pronounced, and occurred prior to, significant loss of NSE expression in the tissue. Significant increases in cortical GFAP expression were apparent as the disease progressed. No gene expression changes were observed in the cerebellum, which is relatively spared of AD neuropathology. CONCLUSIONS: This first study to quantify ZnT3 mRNA levels in human pm brain tissue from individuals with AD and controls has revealed a significant loss of ZnT3 expression in cortical regions, suggesting that neuronal cells in particular show reduced expression of ZnT3 mRNA in the disease. This suggests that altered neuronal Zn(2+ )handling may be an early event in AD pathogenesis.